2001
DOI: 10.1177/154193120104502305
|View full text |Cite
|
Sign up to set email alerts
|

Visual Demand of Driving and the Execution of Display-Intensive in-Vehicle Tasks

Abstract: To gain insight as to when telematics can be distracting, 16 participants drove a simulator on roads with long curves of several different radii. Participants read electronic maps displayed in the center console while both parked and driving. In separate trials, the visual demand/workload of the same straight and curved sections was measured using the visual occlusion technique. Visual demand was correlated with inverse curve radius.As visual demand increased, driving performance declined. Participants made sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
2
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 1 publication
8
68
2
4
Order By: Relevance
“…Second, whereas the selfpaced occlusion paradigm allowed visual sampling strategies to be measured, it is not a suitable substitute for eye tracking. The occlusion method, however, is commonly used to measure and estimate visual demand (e.g., Baumann, Keinath, Krems, & Bengler, 2004) and the average occlusion period durations in this study were similar to glance durations observed in previous research (Tsimhoni & Green, 2001). …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Second, whereas the selfpaced occlusion paradigm allowed visual sampling strategies to be measured, it is not a suitable substitute for eye tracking. The occlusion method, however, is commonly used to measure and estimate visual demand (e.g., Baumann, Keinath, Krems, & Bengler, 2004) and the average occlusion period durations in this study were similar to glance durations observed in previous research (Tsimhoni & Green, 2001). …”
Section: Discussionsupporting
confidence: 86%
“…The average duration of participants' first three occlusion periods was not significantly different across number entry stimuli. On average, participants only occluded the roadway between 1 and 1.2 seconds, durations that have been found in previous visual sampling research (Tsimhoni & Green, 2001). This suggests that participants were using a similar visual sampling strategy for each number entry stimulus regardless of sub-task size.…”
Section: Discussionsupporting
confidence: 64%
“…According to Tsimhoni and Green (2001), the addition of a secondary task while driving significantly impairs driving performance, which could not be confirmed in this study. Probably due to the simplicity of the secondary task used which was not sufficient to cause extra workload to yield any differences in lane keeping or stress.…”
Section: Discussioncontrasting
confidence: 80%
“…Automobiles are becoming more and more technologically complex (Baber & Wankling, 1992;Noy, 1997) with more and more built-in driver information systems (Tsimhoni & Green, 2001). This also increases the amount, and range, of information presented to the driver, which leads to the use of dynamic displays showing many types of information in one place (Baber & Wankling, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation